Revascularization of the humeral artery with a vein saphenous inverted in vascular trauma by stabbing - Osvaldo Valdés Dupeyrón; Gino Kleiver Alvia Del Castillo; Javier González Robles; Josselyn Soraya Jalil Gorozabel; Andrea Vanesa Bazurto Zambrano; Nicole Stephania Roldan Macias (Revista Cubana de Medicina Militar)
Introduction: The vascular traumatisms of the limbs are very frequent at present. When these injuries do not receive the required care they can evolve to serious complications, which includes the loss of the limb or death. Objective: To describe the brachial artery repair technique using the saphenous vein in a case with brachial artery trauma with vascular compromise. Clinical case: 37-year-old patient with a history of psychiatric illness, with a diagnosis of a stab wound with vascular compromise in the left forearm of four hours of evolution. On admission, he was unstable, hypovolemic shock, with cyanotic limb and absence of distal pulses. Intravenous antibiotics, crystalloid solution and blood were indicated. The patient was transferred to the surgery and a total section of the brachial artery was found. The revascularization technique was performed with an inverted saphenous vein graft. The patient evolved favorably and was discharged on the third day. Eleven months later, Doppler ultrasound was performed and good graft patency was confirmed. Conclusions: The inverted saphenous vein revascularization technique contributed satisfactorily to the survival and quality of life of the treated case.